Local Community Agency and Vulnerability Influences on a Montana Wildfire. Issue 2 (21st January 2019) - Carroll, Matthew S; Paveglio, Travis
Abstract: This case study explores the social dynamics surrounding a destructive wildfire in central Montana. We examine the settlement patterns and events that respondents felt helped create high social vulnerability among a significant portion of local residents in the study area and the way that vulnerability led to impacts from the fire. We also examine the local experience of the fire itself and the recovery process that followed. Our results suggest that the social vulnerability to this particular event was decades in the making for a significant subset of local residents. The development of a local culture that was individualistic and wary of outside aid or programs, and that did not necessarily develop close community ties helped to set the stage for impacts from wildfire. We also discuss how nearby community support and recovery from the wildfire were influenced by accumulated experience with other hazards and a "coming together" of local populations. We discuss how this case adds to existing literature on social vulnerability to wildfire, arguing that the conditions that led to the social consequences in this particular case may be useful in other regions of the US West and beyond.